2017
DOI: 10.1021/acs.energyfuels.6b02807
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Shale Oil Hydrotreatment with Composition Analysis Using Positive-Ion Mode Atmospheric Pressure Photoionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Positive-ion mode of atmospheric pressure photoionization (APPI) coupled with a 9.4 T Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer has been applied to the characterization of shale oil from pyrolysis and its hydrotreatment. The hydrotreated shale oil was obtained through reactions over catalysts Ni−Mo, Ni−W, or Co−Mo. It was found that N 1 and N 1 O 1 species are the dominant N compounds and S 1 species is the dominant S compound in shale oil from pyrolyzing Huadian oil shale. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The abundance of the nitrogen-containing compounds was found to be significantly reduced upon both HDT and FCC. These results were in agreement with those of Zhang et al, who employed (+) APPI 9.4 T FTICR MS to show that nitrogen- and sulfur-containing compounds were effectively removed from a shale oil upon HDT using a NiMo-based catalyst …”
Section: Applicationssupporting
confidence: 91%
See 1 more Smart Citation
“…The abundance of the nitrogen-containing compounds was found to be significantly reduced upon both HDT and FCC. These results were in agreement with those of Zhang et al, who employed (+) APPI 9.4 T FTICR MS to show that nitrogen- and sulfur-containing compounds were effectively removed from a shale oil upon HDT using a NiMo-based catalyst …”
Section: Applicationssupporting
confidence: 91%
“…These results were in agreement with those of Zhang et al, who employed (+) APPI 9.4 T FTICR MS to show that nitrogen-and sulfur-containing compounds were effectively removed from a shale oil upon HDT using a NiMo-based catalyst. 113 Models that can predict the total nitrogen content in crude oil before and after a treatment based on measured mass spectra would be useful in determining the efficiencies of different treatments. Terra et al utilized partial least-squares regression with variable selection based on competitive adaptive reweighted sampling (CARSPLS) to create a model for the prediction of the content of basic nitrogen compounds in crude oils based on data obtained using (+) LDI 9.4 T FTICR MS. 114 The model was built based on the relative abundances of molecular ions of 48 basic nitrogen-containing compounds in the mass spectra measured for 50 crude oils.…”
Section: Sophisticated Instrumentation Requiredmentioning
confidence: 99%
“…In HDS, it was reported that the C–S bonds in the sulfur-containing compounds were cleaved by the addition of hydrogen (H) and were converted into HCs. By comparing Figures and in the case of AR1/tAR1 and AR2/tAR2 samples, it can be deduced that the increased amount of HC compounds in treated oils resulted from the transformation of sulfur compounds during the HDS. Because the sulfur-containing compounds with DBE < 9, are easier to hydrogenolyze than compounds with DBE > 9, benzothiophene-type compounds of DBE values from 6 to 8 and thiophinobenzothiophene-type compounds of DBE values from 8 to 10 were easily converted into aromatic HCs of DBE values from 4 to 7.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) is considered an effective method to identify complex organic compounds in various petroleum fractions, especially heavier fractions. Different ionization sources, such as atmospheric pressure photoionization (APPI) and electrospray ionization (ESI) coupled with FT-ICR MS, having advantages of high resolution and good sensitivity, have been successfully utilized to identify hydrocarbons, non-hydrocarbons, and metal compounds in a variety of petroleum fractions. Different compounds in heavy petroleum fractions can be ionized by different techniques, but the effect on others is not obvious. Because APPI is a nonselective method that can ionize many types of molecules, it provides a general overview of the species in heavy petroleum fractions, whereas ESI is more selective for polar species and presents a basic character in the positive mode and an acidic character in the negative mode.…”
Section: Introductionmentioning
confidence: 99%